The phenomenon of gambling considered in the context of adolescent psychosocial functioning - Rzeszutko, Ewa (Current Problems of Psychiatry, 2013)
The main purpose of this article is to examine the contribution of certain psychosocial variables to the development of serious gambling problems among adolescents. This article includes a description of risk and protective factors associated with youth gambling problem. Gambling has become a popular leisure activity among youth. Similar to adults, most adolescents gamble responsibly, primarily for purposes of entertainment and recreation, and without experiencing serious problems. Nevertheless, there is a small but significant proportion of youth who gamble excessively and experience serious negative psychological, social, financial costs. CBOS statistics indi-cate that gambling problem concerns not only adults, but also adolescents. Findings from adult gambling research suggest that demo-graphic, individual, family, peer variables are important correlates of risky and pathological gambling in adolescents